Nuclear zirconium – the basis of alloys with improved neutron-physical, radiation, and corrosion properties - Mukhachev, A.P.; Pylypenko, M.M.; Kharуtonova, O.A. (Вопросы атомной науки и техники, 2020)
The paper provides a review of industrial technologies for the production of nuclear zirconium. Their advantages and disadvantages have been shown, a comparative analysis of the quality of zirconium and hafnium salts has been given. Zirconium with a purity of 99.95%, is on a par with the quality of the iodide metal, with a hafnium content of less than 0.005%, was obtained from zirconium tetrafluoride (TFZ) by electrolysis and method of salt recovery with calcium.